2023
DOI: 10.3389/fbioe.2023.1018012
|View full text |Cite
|
Sign up to set email alerts
|

LIPUS as a potential strategy for periodontitis treatment: A review of the mechanisms

Abstract: Periodontitis is a chronic inflammatory condition triggered by oral bacteria. A sustained inflammatory state in periodontitis could eventually destroy the alveolar bone. The key objective of periodontal therapy is to terminate the inflammatory process and reconstruct the periodontal tissues. The traditional Guided tissue regeneration (GTR) procedure has unstable results due to multiple factors such as the inflammatory environment, the immune response caused by the implant, and the operator’s technique. Low-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 143 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…Low-intensity pulsed ultrasound (LIPUS) is a type of special ultrasound, recent study had found could promote cartilage repair after damage and suspend cartilage degeneration 15 . Furthermore, LIPUS converts acoustic signals into mechanical signals to trigger a series of cellular responses that enhancing gene expression and anti-in ammatory responses in mature chondrocytes 16,17 . At the same time, relevant research shown that LIPUS could regulate the expression level of YAP in certain condition 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Low-intensity pulsed ultrasound (LIPUS) is a type of special ultrasound, recent study had found could promote cartilage repair after damage and suspend cartilage degeneration 15 . Furthermore, LIPUS converts acoustic signals into mechanical signals to trigger a series of cellular responses that enhancing gene expression and anti-in ammatory responses in mature chondrocytes 16,17 . At the same time, relevant research shown that LIPUS could regulate the expression level of YAP in certain condition 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that low-intensity pulsed ultrasound (LIPUS), a special type of ultrasound can promote cartilage repair after damage and slow down cartilage degeneration [17]. Furthermore, LIPUS converts acoustic signals into mechanical signals, which then trigger a series of cellular responses [18,19]. For example, LIPUS has been reported to treat periodontitis and neurological diseases owing to its anti-inflammatory effect [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%